2,2'-[2,4-Bis(naphthalen-1-yl)cyclobutane- 1,3-diyl]bis(1-methylpyridinium) bis(4-chlorobenzenesulfonate): thermalinduced [2 + 2] cycloaddition reaction of a heterostilbene - Chantrapromma, Suchada; Chanawanno, Kullapa; Boonnak, Nawong; Hoong, Kun Fun (International Union of Crystallography, 2014)
The asymmetric unit of the title salt, C36H32N2 2+- 2C6H4ClO3S, consists of one anion and one half-cation, the other half being generated by inversion symmetry. The dihedral angle between the pyridinium ring and the napthalene ring system in the asymmetric unit is 42.86 (6). In the crystal, cations and anions are linked by weak C—H...O interactions into chains along [010]. Adjacent chains are further arranged in an antiparallel manner into sheets parallel to the bc plane. – interactions are observed involving the cations, with centroid–centroid distances of 3.7664 (8) and 3.8553 (8) A ° .